THE INFLUENCE OF UNDERSTANDING ACCOUNTING STANDARDS, TRANSPARENCY, ACCOUNTABILITY, AND INFORMATION TECHNOLOGY ONIMPLEMENTATION OF PRESENTATION OF FINANCIAL REPORTS BASED ON ISLAMIC BOARDING SCHOOL ACCOUNTING GUIDELINES - Hendra Raza; Sajida Khairullah; Rico Nur Ilham (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to examine the effect of human resource competence (HR), transparency, accountability, and information technology as independent variables, and the presentation of Islamic boarding school accounting-based financial reports as the dependent variable on the dayah in Lhokseumawe City. This type of research includes quantitative research. The population in this study amounted to 68 dayah. The sampling technique used purposive sampling, namely the technique of determining the sample with certain considerations and using the slovin formula so that the sample was 40 dayah. Methods of data collection is done by distributing questionnaires. The analytical method used is multiple linear regression analysis technique with SPSS 26. The results show that simultaneously, competence of human resources (HR), transparency, accountability and information technology influence the presentation of Islamic boarding school accounting-based financial reports. Partially, the variable human resources (HR) has a positive and significant effect on the presentation of Islamic boarding school accounting-based financial reports, while the transparency variable has no effect on the presentation of Islamic boarding school accounting-based financial reports, while accountability and information technology have both a negative and a significant positive effect on the presentation Islamic boarding school accounting-based financial reports.